Maximal Strength, Sprint, and Jump Performance in High-Level Female Football Players Are Maintained With a Customized Training Program During the COVID-19 Lockdown - Pedersen, Sigurd; Johansen, Dag; Casolo, Andrea; Randers, Morten B.; Sagelv, Edvard H.; Welde, Boye; Winther, Andreas Kjæreng; Pettersen, Svein Arne (Frontiers in Physiology, 2021)
Introduction: The COVID-19 outbreak with partial lockdown has inevitably led to an alteration in training routines for football players worldwide. Thus, coaches had to face with the novel challenge of minimizing the potential decline in fitness during this period of training disruption. Methods: In this observational pre- to posttest study involving Norwegian female football players (18.8 ± 1.9 yrs, height 1.68 ± 0.4 m, mass 61.3 ± 3.7 kg), we investigated the effects of a prescribed home-based and group-based intervention, implemented during the COVID-19 lockdown, on maximal muscular force production and high velocity. Specifically, maximal partial squat strength (1RM), counter movement jump (CMJ) and 15 m sprint time were assessed one week prior the lockdown and 12 weeks after the onset of lockdown. We also collected training content and volume from the prescribed training program and self-reported perceived training quality and motivation towards training. Results: We observed no change in 1RM (pretest: 104 ± 12 kg, posttest: 101 ± 11 kg (P = 0.28)), CMJ height (pretest: 28.1 ± 2.3 cm, posttest: 26.8 ± 1.9 (P = 0.09)) and 15 m sprint time (pretest: 2.60 ± 0.08 s, posttest: 2.61 ± 0.07 s (P = 0.52)). Conclusion: Our findings suggest that a prescribed home-based and group based intervention with increased training time devoted to strength, jump and sprint ability, and regulated to obtain a sufficient infection control level is feasible and effective to preserve strength, jumping and sprinting abilities of high-level female football players during a ̴ 3-month period of a pandemic-induced lockdown.